5 L급 액체수소 저장용기의 성능특성 연구 - 강상우; 나다니엘 가르소; 임창무; 백종훈; 김서영; 오인환 (한국수소및신에너지학회, 2015)
In the face of the world’s growing energy storage needs, liquid hydrogen offers a high energy density solution for the storage and transport of energy throughout society. A 5 L liquid hydrogen storage tank has been designed, fabricated and tested to investigate boil-off rate of liquid hydrogen. As the insulation plays a key role on the cryogenic vessels, various insulation methods have been employed. To reduce heat conduction loss, the epoxy resin-based insulation supports G-10 were used. To minimize radiation heat loss, vapor cooled radiation shield, multi-layer insulation, and high vacuum were adopted. Mass flow meter was used to measure boil-off rate of the 5 L cryogenic vessel. A series of performance tests were done for liquid nitrogen and liquid hydrogen to compare with design parameters, resulting in the boil-off rate of 1.7%/day for liquid nitrogen and 16.8%/day for liquid hydrogen at maximum.